(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
This article considers the process of forming professional qualities in students as a pedagogical problem. Professional qualities are a set of personal and social characteristics that students need to succeed in their profession and have a significant impact on their future professional activities. The article discusses the current pedagogical problems of forming professional qualities, the difficulties in guiding students to a profession, and the role of teachers.